Outcomes of Cancer Patients Affected by COVID‐19 in Different Settings: A Retrospective Study in Lebanon - Ahmad El Mahmoud; Elie Jean Karam; Reine Abou Zeidane; Wafaa Khaled; Youssef Zougheib; Joe David Azzo; Hussein El Jebbawi; Ali Atoui; Razan Mohty; Tasnim Diab; Iman Abou Dalle; Maya Charafeddine; et al. (Cancer Reports)
ABSTRACT Background The diverse presentation of COVID‐19 symptoms and outcomes has revealed a significant gap in understanding the specific risk factors and characteristics of the virus among immunocompromised cancer patients, particularly in the Middle East. Aims We our study aimed to address this gap by investigating the characteristics and outcomes of COVID‐19 in cancer patients compared to non‐cancer patients. Methods and Results We carried out a retrospective analysis, collecting demographic, oncologic, and COVID‐19‐related data from electronic medical records of 248 patients admitted to our tertiary care center in Lebanon. Statistical analysis was conducted using SPSS to identify patterns. Patients with solid tumors were 3.433 times more likely to die than those who were cancer‐free (p = 0.012). Moreover, patients with advancing disease were 2.805 times more likely to be admitted to the ICU (p = 0.03) and 14.7 times more likely to die (p < 0.001) compared with those in remission. Conclusion Our findings emphasize the critical need for tailored preventive measures and specialized care for immunocompromised cancer patients, given their heightened vulnerability to severe COVID‐19 outcomes. These insights contribute to the development of specific strategies aimed at enhancing the protection and clinical management of this high‐risk group.